Organic, mineral and organomineral fertilizer in the growthof wheat and chemical changes of the soil. - MUMBACH, G. L. (2019)
The organomineral fertilizers can release organic compounds during their solubilization, and those compounds can affect the plant growth. The aim of this study was to evaluate the initial development of wheat, nutrient accumulation in the plant and soil chemical changes, with the use of organic, mineral and organomineral fertilizers. The experiment was conducted in a greenhouse using an Acrisol cultivated with wheat (Triticum aestivum). Six treatments were tested: 100% of the nutrient recommendation in organomineral form (OMF 100); broiler litter in the same amount present in the OMF 100 (BL 10); mineral fertilizer in the same quantity present in the OMF 100 (MF 90); 100% of the nutrient recommendation in the form of broiler litter (BL 100); 100% of the nutrient recommendation in mineral form (MF 100); and a control without fertilization (CONT). The treatments were evaluated at six sampling times: 2, 4, 8, 15, 30 and 80 days after implantation. No significant differences were observed between fertilizers in dry matter yield. In the soil, there was a decrease in availability of N, P and K over time. By equivalence, all the sources tested can be used in the supply of nutrients to the wheat crop.Key words:biofertilizer; broiler litter; fertilization; Triticum aestivu